The Islamic Education System during the Era of the Rightly Guided Caliphs: The Foundation of Islamic Civilization Development - Busahdiar Busahdiar; Rabiatul Adawiyah; Novita Fauziah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the Islamic education system during the era of the Rightly Guided Caliphs and to examine its contribution to the development of Islamic civilization. Employing a qualitative library research approach, this study analyzes classical Islamic literature, historical records, and contemporary scholarly works concerning educational philosophy, curriculum, educational institutions, teaching methods, educational leadership, and educational policies implemented during the reigns of Abu Bakr al-Ṣiddīq, Umar ibn al-Khaṭṭāb, Uthman ibn Affān, and Ali ibn Abi Ṭālib. The findings indicate that Islamic education during this period developed into a systematic educational model characterized by the integration of spiritual, intellectual, moral, and social dimensions. Educational institutions such as mosques and kuttab became centers for knowledge transmission, while the standardization of the Qur'an, expansion of scholarly networks, appointment of teachers, and establishment of educational centers significantly strengthened Islamic intellectual development. Furthermore, each caliph introduced distinctive educational policies that collectively contributed to preserving Islamic teachings and fostering scientific advancement. The study concludes that the Islamic education system during the era of the Rightly Guided Caliphs established the essential educational foundations for the flourishing of Islamic civilization and continues to offer valuable educational principles for contemporary Islamic education.